PENGARUH KOLEKTIVISME, KOMITMEN ORGANISASI, DAN PENALARAN MORAL TERHADAP INTENSI MELAKUKAN WHISTLEBLOWING PADA PT. BANK BRI (Persero), Tbk. CABANG BENGKULU - Intan Tri Nurdianti; Fitrawati Ilyas (UNIB Press, 2018)
This research aims to examine the effect of collectivism, organizational commitment, and moral reasoning on whistleblowing intention. The primary data of this research are collected from bank officer at Bank BRI Bengkulu Branch by using a survey approach. The questionnaire distributed to 60 respondents, but only 52 questionnaires that can be analyzed or processed. Analysis of the data in this study using analyzed multiple regression analysis. The result of the research showed that: (1) collectivism has a positive effect on whistleblowing intention, (2) organizational commitment does not affect on whistleblowingintention, and (3) moral reasoning has a positive effect on whistleblowing intention. This research is expected to help the banks, particularly Bank BRI Bengkulu Branch in designing strategies to increase their employees whistleblowing intention or in enhancing the institution’s whistleblowing system by paying attention to factors that influence whistleblowing intentions.Key words: whistleblowing intention, collectivism, organizational commitment, moral reasoning